The Role of Organizational Climate and Quality of Working Life in Improving Employee Performance - Maulana, Achmad Amzal; Ampauleng, Ampauleng; Abdullah, Salma (Jurnal Pemerintahan dan Politik Lokal, 2025)
This study aims to analyze the role of organizational climate and quality of work life in improving employee performance. A conducive organizational climate and a good quality of work life are believed to create a productive work environment, increase motivation, and strengthen employee commitment to the organization. The method used in this study is a quantitative approach with survey techniques on a number of employees at the Human Resources Development Agency (BPSDM) of South Sulawesi Province. Data analysis was carried out using Partial Least Square Analysis (PLS) is a variant-based structural equation analysis (SEM) that can simultaneously test measurement models as well as structural model tests to test causality relationships between latent variables constructed. The results of the study show that the quality of work life has a significant effect on employee performance, the organizational climate has a significant effect on employee performance. This shows that efforts to improve employee performance should be focused on improving the quality of work life, such as improving work balance and supportive working conditions. These findings indicate the importance of management's efforts in creating a supportive work culture and providing facilities and policies that support work-life balance for employees so that performance can improve.